TESTS AS DRIVERS OF CHANGE IN EDUCATION: CONTEXTUALISING WASHBACK, AND THE POSSIBILITY OF WASH-FORWARD - Allan, Gordon (VNU Journal of Foreign Studies, 2020)
Whilst the primary aim of tests is to measure ability, it is not uncommon for tests to be deployed in education systems with the intention, at least in part, of driving change in educational practice by making demands that teachers and learners are expected to meet. Washback is one way by which teaching and learning practices may adapt to a new test, but it is not the only possibility and often fails to occur as intended. This paper seeks to draw together ideas from different sources to place washback in the context of other possibilities. The concepts of adaptive implementation and programmed implementation are taken from Henrichsen’s hybrid model of the diffusion/implementation of innovation in education systems. Washback is shown to act in parallel to but distinct from programmed implementation. The picture is completed with van Lier’s concept of wash-forward, first outlined in 1989 but subsequently neglected in the literature. Wash-forward is illustrated with an example from the implementation of the National Matriculation English Test (NMET) in China. The intention is to provide an easily visualised, refreshed and more complete perspective on the processes operating when a new test is introduced as part of a strategy aimed at driving changes in teaching and learning practices; a scenario which is very relevant to the current movement towards four-skills English testing in East Asia and around the world.